Biochemical characterization of legume seeds as ingredients in animal feed - Martín-Pedrosa, Mercedes; Varela, Alejandro; Guillamon, Eva; Cabellos, Blanca; Burbano, Carmen; Gomez-Fernandez, Jose; de Mercado, Eduardo; Gomez-Izquierdo, Emilio; Cuadrado, Carmen; Muzquiz, Mercedes (Spanish Journal of Agricultural Research, 2016)
The current European protein deficit is estimated as high as 70% of present needs. Because of the high protein content of their seeds, grain legumes are attractive candidates for lowering the deficiency in plant protein production. The objective of this work was to identify new sources of vegetable protein that would reduce our high dependence of soy, the main source of protein in the manufacture of feedstuffs. To achieve this goal, we determined the proximate composition, the bioactive components, as well as the antinutritional factors present in the studied seeds. In general, the protein, fat and carbohydrates content of legume seeds studied were within the limits found in the literature. The bioactive compounds detected in all the seeds were α-galactosides, myoinositol phosphates, protease inhibitors and phenols. IP6 (phytic acid) was the main inositol phosphate form in all the samples. The highest protease inhibitors content was detected in both Lathyrus cicera cultivars. Vicia ervilia and L. cicera cultivars showed low haemagglutinating activity (20.4 HU/g). The γ-glutamyl-S-ethenyl-cysteine content in Vicia narbonensis was around 16.0 mg/g. Both L. cicera varieties presented similar β-N-oxalyl-L-α, β-diaminopropionic acid content (0.80 mg/g). The two V. ervilia varieties showed high canavanine concentration (1.93-5.28 mg/g). Vicine was only detected in V. narbonensis cultivars (0.3 mg/g). The biochemical characterization carried out in this study allows us to know the limits of inclusion of these minor crop seeds in feed formulations in order to replace the soybean.